2007
DOI: 10.2341/06-135
|View full text |Cite
|
Sign up to set email alerts
|

Eight In-office Tooth Whitening Systems Evaluated In Vivo: A Pilot Study

Abstract: Clinical RelevanceRapid bleaching is the main advantage of in-office bleaching; however, there is also a rapid reversal that occurs with most in-office products after bleaching. SUMMARYThis in vivo pilot study evaluated eight products with hydrogen peroxide (HP) concentrations ranging from 15% to 35%. The treatment contact time varied from 15 minutes to 60 minutes. Patients were evaluated for color at baseline, immediately after treatment and at one, two, four and six weeks after treatment using a colorimeter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
3
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 9 publications
(8 reference statements)
7
104
3
16
Order By: Relevance
“…All patients were selected according to inclusion and exclusion criteria (Table 1). 1,3,4,[21][22][23] …”
Section: Methodsmentioning
confidence: 99%
“…All patients were selected according to inclusion and exclusion criteria (Table 1). 1,3,4,[21][22][23] …”
Section: Methodsmentioning
confidence: 99%
“…This might explain the results of some in vivo studies, which showed that long-term colour retention of bleached teeth is less stable. Matis et al [18] found a mean ΔE reversal of 65% after 6 weeks [18] and of 50% after 6 months post-bleaching [17]. In contrast, other studies reported only slight colour changes of bleached teeth in the 6 months post bleaching period [3,25].…”
Section: Discussionmentioning
confidence: 99%
“…Included are two studies where the authors tested the null hypothesis that there are no differences between the effectiveness of different in-office products. [18][19] The null hypothesis that there was no difference between the efficacy of using whitening strips compared with whitening wraps was tested in one study. 13 The last of the nine studies was accomplished to determine the efficacy and clinical safety of 10% CP and was accomplished using a placebo vs 10% CP in separate subjects.…”
Section: Comparable Studiesmentioning
confidence: 99%
“…18 The third study used eight products containing anywhere from 15%-40% HP. 19 The eight products were used for various periods of time ( Table 1). …”
Section: In-office Bleachingmentioning
confidence: 99%
See 1 more Smart Citation